Acousto-optic laser projection systems for displaying TV information. (30th April 2015) - Gulyaev, Yu V; Kazaryan, M A; Mokrushin, Yu M; Shakin, O V
Abstract This review addresses various approaches to television projection imaging on large screens using lasers. Results are presented of theoretical and experimental studies of an acousto-optic projection system operating on the principle of projecting an image of an entire amplitude-modulated television line in a single laser pulse. We consider characteristic features of image formation in such a system and the requirements for its individual components. Particular attention is paid to nonlinear distortions of the image signal, which show up most severely at low modulation signal frequencies. We discuss the feasibility of improving the process efficiency and image quality using acousto-optic modulators and pulsed lasers. Real-time projectors with pulsed line imaging can be used for controlling high-intensity laser radiation.